Facing the future - Jenkins, Jerry B.; LaHaye, Tim F. (Wheaton, Ill. : Tyndale House, 1998)
Judd, Lionel, Vicki, and Ryan, four young people who have accepted Jesus as their savior after being left behind on Earth in God's Rapture, struggle to learn how to deal with the coming Tribulation and the Antichrist.
5.0
5-8
Keywords: Christian life -- Fiction; Eschatology -- Fiction; Friendship -- Fiction; Christian life -- Fiction; End of the world -- Fiction; Friendship -- Fiction